If there is dissipation the particle can gain energy - De Carvalho, R Egydio [UNESP] (IOP Publishing, 2015)
In this work, we summarize two different mechanisms to gain energy from the presence of dissipation in a time-dependent non-linear system. The particles can gain energy, in the average, from two different scenarios: i) for very week dissipation with the creation of an attractor with high velocity, and ii) in the opposite limit, for very strong dissipation, the particles can also gain energy from a boundary crisis. From the thermodynamic viewpoint both results are totally acceptable.